2015
DOI: 10.1186/s40478-015-0251-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced β-amyloid pathology in an APP transgenic mouse model of Alzheimer’s disease lacking functional B and T cells

Abstract: IntroductionIn Alzheimer’s disease, accumulation and pathological aggregation of amyloid β-peptide is accompanied by the induction of complex immune responses, which have been attributed both beneficial and detrimental properties. Such responses implicate various cell types of the innate and adaptive arm of the immunesystem, both inside the central nervous system, and in the periphery. To investigate the role of the adaptive immune system in brain β-amyloidosis, PSAPP transgenic mice, an established mouse mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 74 publications
3
42
0
1
Order By: Relevance
“…Brain amyloidosis promotes T cell migration into the brain and the expression of vascular adhesion molecules in brain vessels ( Ferretti et al, 2016 ). Cells of the adaptive immune system play a negative role during AD, and APP/PS1 transgenic mice crossbred with recombination activating gene 2 (RAG2) knockout mice lacking functional B and T cells are characterized by limited brain Aβ pathology, enhanced microgliosis and the more efficient phagocytosis of Aβ peptide aggregates ( Späni et al, 2015 ). Together, these data suggest that activated T cells play a detrimental role in AD pathology and that interfering with activated T cell development or activity may have a beneficial impact.…”
Section: Leukocyte Trafficking During Admentioning
confidence: 99%
“…Brain amyloidosis promotes T cell migration into the brain and the expression of vascular adhesion molecules in brain vessels ( Ferretti et al, 2016 ). Cells of the adaptive immune system play a negative role during AD, and APP/PS1 transgenic mice crossbred with recombination activating gene 2 (RAG2) knockout mice lacking functional B and T cells are characterized by limited brain Aβ pathology, enhanced microgliosis and the more efficient phagocytosis of Aβ peptide aggregates ( Späni et al, 2015 ). Together, these data suggest that activated T cells play a detrimental role in AD pathology and that interfering with activated T cell development or activity may have a beneficial impact.…”
Section: Leukocyte Trafficking During Admentioning
confidence: 99%
“…The peripheral immune system is clearly implicated in AD pathogenesis (Heneka et al, ; Prinz & Priller, ). However, multiple contradictory studies indicate that the relative contributions of adaptive and innate immunity to AD pathogenesis is poorly understood; and whether and how these systems should be modulated to improve AD pathology is unclear (Alves et al, ; Browne et al, ; Dansokho et al, ; Marsh et al, ; Spani et al, ; Yang, Yang, Xie, Wei, & Bi, ; Zenaro et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the blood-derived leukocyte subpopulations, monocytes migrate into the brain in animal models of AD and their presence is associated with Aβ clearance (30,31). T cells are also present in the brains of AD patients, but their role appears to depend on the T cell subset and the disease phase (10,(32)(33)(34)(35). Vascular inflammation and the trafficking of immune system cells have recently been implicated in the pathogenesis of AD, based on studies showing that neutrophils invade the brain and contribute to the induction of cognitive dysfunction and the neuropathological hallmarks of AD (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Rag-5xFAD mice lacking T, B and natural killer (NK) cells have a greater Aβ burden and more severe gliosis and neuroinflammation (35). However, another study using APP/PS1 transgenic mice produced contradictory results, i.e., the Rag-PSAPP mice showed evidence of increased Aβ clearance-probably mediated by microglial cells-, suggesting that adaptive immunity has a negative role during AD (33). The only link between these two studies is that adaptive peripheral cell populations were found to act in concert with microglial cells.…”
Section: Adaptive Immune Cells In Admentioning
confidence: 99%